Good Governance in the Management of Early Childhood Education Grants by Regional Government - Puspa Ayu Widhi Pangestu; Priyanto Priyanto; Ulul Albab; Sri Kamariyah (International Journal of Humanities and Social Sciences Reviews, 2026)
This study aims to analyze the application of good governance principles in the management of ECE grants by regional governments, focusing on aspects of transparency, accountability, public participation, and legal certainty. The study employs a qualitative approach using Qualitative Secondary Analysis (QSA), analyzing various secondary data sources such as policy documents, government reports, previous research findings, and relevant academic literature on education grant management. Data analysis was conducted systematically through data reduction, categorization, interpretation, and conclusion drawing. The results indicate that the implementation of transparency in ECE grant management is reflected in the openness of information regarding grant application procedures, recipient selection mechanisms, and fund usage reporting. Accountability is realized through administrative and financial accountability mechanisms that must be fulfilled by both regional governments and ECE institutions receiving the grants. Public participation is evident from the involvement of communities, ECE institution managers, and parents in the planning, implementation, and supervision of the grant program. Meanwhile, legal certainty in grant management is demonstrated by the existence of regulations that clearly govern grant provision mechanisms, fund disbursement procedures, and obligations for reporting and accountability in fund utilization. The study concludes that the application of good governance principles in the management of ECE grants by regional governments plays a crucial role in enhancing transparency, accountability, and effectiveness in educational fund management. Furthermore, community involvement and regulatory certainty serve as key supporting factors in achieving better governance of education grants.